2008
DOI: 10.1556/avet.56.2008.2.5
|View full text |Cite
|
Sign up to set email alerts
|

Effect of DGAT1 and TG gene polymorphisms on intramuscular fat and on milk production traits in different cattle breeds in Hungary

Abstract: The objective of this study was to estimate the effect of the thyroglobulin (TG) locus on beef quality traits in some beef cattle breeds and to investigate the effect of the DGAT1 locus on milk production traits in the Hungarian Holstein Friesian population. TG and DGAT1 genotypes were determined by polymerase chain reaction-restriction fragment length polymorphism (PCR-RFLP) assay. At the TG locus TT bulls showed the highest fat percentage values in the longissimus dorsi muscle (m. longissimus dorsi); the dif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
9
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 26 publications
(12 citation statements)
references
References 10 publications
2
9
0
Order By: Relevance
“…Production levels for both Fleckvieh and Braunvieh genotypes are consistent with those previously reported by Anton et al [13] and Pilarczyk et al [14] for dual-purpose European breeds. However, given the better performance of the Fleckvieh breed (+353.5 kg) we could estimate that on identical housing and feeding conditions, the farm returns are higher with 91.55 EUR/year/cow, compared to Braunvieh cows (0.259 EUR/kg of milk) [15].…”
Section: Resultssupporting
confidence: 90%
“…Production levels for both Fleckvieh and Braunvieh genotypes are consistent with those previously reported by Anton et al [13] and Pilarczyk et al [14] for dual-purpose European breeds. However, given the better performance of the Fleckvieh breed (+353.5 kg) we could estimate that on identical housing and feeding conditions, the farm returns are higher with 91.55 EUR/year/cow, compared to Braunvieh cows (0.259 EUR/kg of milk) [15].…”
Section: Resultssupporting
confidence: 90%
“…Values concerning the effect of different TG genotypes of bulls on the fat content of LD are similar to our previous results obtained in Hungarian beef cattle (Anton et al, 2008). Distribution of the presented leptin genotype frequency values correspond to those obtained by Nkrumah et al (2005).…”
Section: Resultssupporting
confidence: 89%
“…addition, the C allele had trend to increase marbling score trait. Anton et al (2012) reported that homozygote CC animals in the TG/BstYI gene had the highest of milk yield than other genotype animals in Jersey and Hungarian Simmental populations (P<0.05). Bonilla et al (2010) reported that homozygote CC animals in the TG/BstYI gene of Mexican beef population had lowest of intramuscular fat content (IMF) than heterozygote animals (P<0.05).…”
Section: Resultsmentioning
confidence: 96%